2004
DOI: 10.1159/000076917
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Pentoxifylline on Volume-Induced Lung Injury in Newborn Piglets

Abstract: To evaluate the efficacy of pentoxifylline (PTXF) in the attenuation of lung inflammation during volume-induced lung injury (VILI) in newborn piglets, 17 newborn piglets were mechanically ventilated with a large tidal volume (50 ml/kg) for a period of 8 h. They were randomly assigned to a placebo (PL, n = 9) or a treatment group (PTXF, n = 8) that received PTXF (20 mg/kg as a bolus, followed by a continuous infusion of 5 mg/kg/h). Hemodynamics, lung mechanics and arterial blood gases were measured during the 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
(28 reference statements)
1
3
0
1
Order By: Relevance
“…In contrast to previous observations (6), a recent study in the animal model of hyperoxic resuscitation after perinatal asphyxia suggested a potential role for N-acetylcysteine in lung protection, as it was proved to reduce lung and systemic levels of OS and inflammatory markers (111). Moreover, pentoxifillyne, a phosphodiesterase inhibitor with immunomodulatory and antifibrotic features, has been investigated in the animal model of hyperoxia, and it was proved to reduce lung edema and neutrophils influx, while it increased lung activity of SOD, CAT, and GPx (9), in agreement with previous reports of reduced inflammatory cytokines in tracheal aspirates (173) and lung protection against mechanical ventilation-induced injury (81,158). Besides antioxidant activity, pentoxyfilline also induces VEGF expression and enhances pulmonary vasculature development (9), which could be a major issue for the prevention of BPD-associated vascular abnormalities.…”
Section: Melatonin and Other Antioxidantssupporting
confidence: 78%
“…In contrast to previous observations (6), a recent study in the animal model of hyperoxic resuscitation after perinatal asphyxia suggested a potential role for N-acetylcysteine in lung protection, as it was proved to reduce lung and systemic levels of OS and inflammatory markers (111). Moreover, pentoxifillyne, a phosphodiesterase inhibitor with immunomodulatory and antifibrotic features, has been investigated in the animal model of hyperoxia, and it was proved to reduce lung edema and neutrophils influx, while it increased lung activity of SOD, CAT, and GPx (9), in agreement with previous reports of reduced inflammatory cytokines in tracheal aspirates (173) and lung protection against mechanical ventilation-induced injury (81,158). Besides antioxidant activity, pentoxyfilline also induces VEGF expression and enhances pulmonary vasculature development (9), which could be a major issue for the prevention of BPD-associated vascular abnormalities.…”
Section: Melatonin and Other Antioxidantssupporting
confidence: 78%
“…Recentemente, tem sido demonstrado na literatura que mediadores inflamatórios, como o FNT-alfa e as interleucinas, aumentam durante a ventilação mecânica, principalmente quando se empregam volumes correntes elevados 13,14,[21][22][23][24][25] . Naik et al observaram que o início da ventilação mecânica em ovelhas prematuras desencadeou o aumento dos níveis de mediadores inflamatórios, sugerindo que bastam alguns ciclos de ventilação mecâ-nica no prematuro para causar a lesão pulmonar 15 .…”
Section: Reação Inflamatóriaunclassified
“…Studies in rabbits have shown increased levels of CAT, SOD, and GPX during ischemia and reperfusion injury after PTX treatment (17). Studies have also shown that PTX is able to attenuate lung injury related to mechanical ventilation and meconium (18,19). In neonatal HILI models, PTX treatment decreased IL-6 concentration in bronchoalveolar lavage (20), reduced alveolar fibrin deposition, and prolonged survival (21).…”
mentioning
confidence: 99%